Réponses

  • Omnes
  • Modérateur confirmé
2014-02-15T18:27:51+01:00
Salut,
1.
A = (5x+1)² - (x-3)(5x+1)
A = (25x² + 10x + 1) - (5x² + x - 15x -3)
A = 25x² + 10x + 1 - 5x² - x + 15x + 3
A = 20x² +24x + 4
2.
A = (5x+1)² - (x-3)(5x+1)
A = (5x+1)[5x+1 - (x-3) ]
A = (5x + 1)(5x + 1 - x + 3)
A = (5x+1)(4x +4)
A = 4(5x+1)(x+1)

3.
A = 4(5x+1)(x+1)
A = 4(5*(-3) + 1)(-3+1)
A = (4*(-15) + 4 )*-2
A = -56 * -2
A = 112
4.

A = 0
4(5x+1)(x+1) = 0
5x + 1 = 0
5x = -1
x = -1/5

x + 1 = 0
x = -1

Bonne soirée!
2014-02-15T19:15:04+01:00
Bonsoir

25x² +10x +1 - 5x² +x -15x -3
20x² -4x -2

(5x +1)(5x+1) - (x-3)
(5x+1)(5x+1 -x +3)
(5x+1)(4x +4)
pour x = -3
(-15 +1)( -12 +4) = -14 x -8 = 112

A = 0
(5x+1)(4x+4) = 0
soit 5x +1 = 0
5x = -1 et x = -1/5
soit 4x +4 = 0
4x = -4
x = -1